Are the Associations of Cardiac Acceleration and Deceleration Capacities With Fine Metal Particulate in Welders Mediated by Inflammation?. Issue 3 (March 2016) - Umukoro, Peter E.; Wong, Jason Y.Y.; Cavallari, Jennifer M.; Fang, Shona C.; Lu, Chensheng; Lin, Xihong; Mittleman, Murray A.; Schmidt, Georg; Christiani, David C.
Abstract : Objective: The aim of this study was to investigate whether associations of acceleration capacity (AC) and deceleration capacity (DC) with metal-PM2.5 are mediated by inflammation. Methods: We obtained PM2.5, C-reactive protein, interleukin (IL)-6, 8, and 10, and electrocardiograms to compute AC and DC, from 45 male welders. Mediation analyses were performed using linear mixed models to assess associations between PM2.5 exposure, inflammatory mediator, and AC or DC, controlling for covariates. Results: The proportion of total effect of PM2.5 on AC or DC (indirect effect) mediated through IL-6 on AC was 4% at most. Controlling for IL-6 (direct effect), a 1 mg/m 3 increase of PM2.5 was associated with a decrease of 2.16 (95% confidence interval −0.36 to 4.69) msec in AC and a decrease of 2.51 (95% confidence interval −0.90 to 5.93) msec in DC. Conclusion: IL-6 may be mediating the effect of metal particulates on AC.